Radiopacity evaluation of composite restorative resins and bonding agents using digital and film x-ray systems - Oztas, Bengi; Kursun, Sebnem; Dinc, Gul; Kamburoglu, Kıvanc (European Journal of Dentistry, 2012)
Objective: The purpose of this in vitro study was to explore the radiopacity of composite resins and bonding materials using film and phosphor plates.Methods: Nine composite dental resin specimens and human tooth slices were exposed together with an aluminium stepwedge using dental film and phosphor plates. Eight dentin bonding specimens were prepared and exposed in a similar manner. Their radiopacity on film was assessed using a transmission densitometer, and the radiopacity with phosphor plates was assessed digitally using the system’s own software (Digora). Data were analysed using one-way analysis of variance (ANOVA) and post-hoc Tukey tests (P<.05). Film and phosphor plate radiopacity values were compared using simple regression analysisResults: Excellent linear correlation was found between film and phosphor plates for both composite resins and bonding agents. The composite materials Spectrum Tph and Natural Look exhibited the highest radiopacity with film and with phosphor plates, respectively. All the dentin bonding agents tested exhibited lower radiopacity than dentin. Conclusion: Synergy, Ice, Filtek Silorane, Filtek Z250, Clearfil Majesty Posterior, Herculite Classic, Spectrum Tph, and Natural Look composite materials exhibited greater radiopacity than dentin, and all the dentin bonding agents tested exhibited lower radiopacity than either enamel or dentin. (Eur J Dent 2012;6:115-122)
Keywords: dental bonding; densitometry; radiography